Analisis Pengembangan Organisasi Pendidikan Tinggi Swasta dengan Model Weisbord (Kasus Universitas Bina Darma Palembang) - Hardiyansyah Herdiansyah (JIANA ( Jurnal Ilmu Administrasi Negara ), 2010)
Organization is a system that continues to process, meaning that thesystem is not static. As the system continues to process the organization has theopportunity to make changes on the input or influence from the surroundingenvironment. For that organization should be open to the inputs available. Allorganizations must be changed because of pressure of internal and externalenvironment of the organization. This study aims to make a diagnosis of theorganization University of Bina Darma Palembang (UBD). Method used is surveymethod with the approach Weisbord. Results of research indicate that the goals andorganization structure has been generally well understood by the UBD lecturers, aswell as the relationship of the existing well has been tied in with the environmentUBD. However, matters relating to the Award, Leadership and GovernanceMechanism job is still running poorly or somewhat problematic.